Preparação e caracterização de um agregado enzimático reticulado (CLEA) de ß- glicosidase produzido por Aspergillus niger - Cunha, Thiago Martins Da (2021)
The enzyme immobilization is a technique that, among some advantages, highlights the feasibility of reusing them and reducing residual contamination in the final product, making biocatalytic processes economically viable. Of the various immobilization protocols, enzymatic immobilization without the use of support by the CLEAs technique (CLEA - cross-linked enzyme aggregation) is very relevant for combining purification and enzymatic immobilization in a single stage, resulting in an immobilized enzyme with a high activity and without bulky support. The enzyme β-glycosidase belongs to the hydrolases class, and has wide industrial use, being applied since the bio-conversion of biomass into glucose for the production of biofuels to the hydrolysis of aroma precursors in the food and beverage industry. To date, few studies have been reported in the literature on the immobilization of microbial β-glycosidases by CLEAs. The objective of the present work was to evaluate the conditions of production of cross-linked enzyme aggregates (CLEAS) of β-glycosidase produced by A. niger and the determination of some biochemical and morphological characteristics of the derivative. For this, the variables of crosslinking agent and spacer agent in immobilization by fungal β-glucosidase CLEAs were studied through the methodology of Complete Factorial Planning 22, with 11 tests (3 central points). The optimal pH and temperatures of activity, pH and temperature of stability and the effect of the concentration of substrate and ions on the activity of the free and immobilized enzyme were determined. The morphological characterization of the derivatives was investigated by Transformed and Fourier Infrared Spectroscopy (FTIR) and by Analytical Thermogravimetry (TG / TGA). The results were published in articles and show a longer term stability of the derivatives and changes in the pH (4.5 to 4.0) and temperature (55 to 60 ° C) of the derivatives compared to the free enzyme. Morphological tests show that the derivatives were more stable at temperature due to the decomposition temperature of 200 ° C for free enzyme and 208 ° C for derivatives.